Dual-tracer PET/CT imaging to determine tumor heterogeneity in a patient with metastatic ACTH-secreting neuroendocrine neoplasm: A case report and literature review - Ryzhkova, Daria; Mitrofanova, Lubov; Tsoy, Uliana; Grineva, Elena; Schlyakhto, Evgeny (Frontiers in Endocrinology, 2022)
Introduction: We present a case of a patient with disseminated ACTH-secreting neuroendocrine neoplasm with biologic heterogeneity between a primary tumor and metastases. The diagnosis was obtained and multidisciplinary management was conducted with a positron emission tomography/computed tomography (PET/CT) scan with Gallium-68 [68Ga]-labeled dodecanetetraacetic acid-tyrosine-3-octreotate ([68Ga]-DOTA-TATE) and Fluor-18 [18F]-fluorodeoxyglucose ([18F]-FDG). Case report: A PET/CT scan revealed a difference between [68Ga]-DOTA-TATE and [18F]-FDG uptake in primary tumor, and several metastases. PET/CT showed high [18F]-FDG uptake and lack of [68Ga]-DOTA-TATE in the primary tumor, whereas both [68Ga]-DOTA-TATE and [18F]-FDG hyperaccumulation were identified in the majority of metastases. Despite positive [68Ga]-DOTA-TATE PET/CT, which is associated with high affinity with somatostatin receptors 2 subtype, immunohistochemical examination revealed overexpression of somatostatin receptors 5 subtype only. Perhaps, this explained ineffectiveness of the treatment with “cold” somatostatin analogues. Conclusion: This case had an aggressive clinical course, in spite of cytoreductive surgical treatment and somatostatin analogue therapy. PET/CT imaging with two tracers is a molecular tool, which demonstrates a biologic heterogeneity between a primary tumor and metastases, and yields additional information that may influence the choice of patient management strategy.